Dye-Sensitized Solar Cells(DSSC) Use Natural Organic Sulphur Cosmos Leaves - Darmawan, Muhammad Iman; Nuzuluddin, Muh. (Universitas Hamzanwadi, 2023)
Energy is a basic need in everyday life, so the need for energy in the world continues to grow. Energy is usually produced from fossils whose existence is diminishing and cannot be renewed. Therefore many experts are looking for ways to make and create some renewable energy, and Dye-sensitized solar cell (DSSC) is one of them. In this study aimed to determine the characterization of the electrical properties of the Dye Sulphur Cosmos (Kenikir Leaf) material extract. The study conducted absorbance tests using a UV Visible 1601 PC Spectrophotometer and current and voltage tests (I-V) using Cathay. These results indicate that some natural dyes from the extraction of natural organic matter have absorbance spectra in the range of 300-800 nm, which have the potential as DSSCs.